PERAN SIZE DALAM MEMODERASI PENGARUH PROFITABILITAS, INVESMENT OPPOURTUNITY COST DAN LEVERAGE TERHADAP KEBIJAKAN DEVIDEN - Moeljono Moeljono; Nasron Alfianto (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
This study aims to determine the effect of profitability, investment opportunity set (IOS), and leverage to dividend policy with moderated size. This study was conducted because there are several previous studies that show that the results of his research there are inconsistencies.The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI). The method of determining the sample is done by purposive sampling method, and based on predetermined criteria, the sample amount is 190 sample of manufacturing company during 2009-2018 period.The analysis technique used is multiple linear regression analysis. To knowthe variable size as a moderate variable or not tested interaction ModeratedReggresion Analysis (MRA).The results show that profitability and leverage are not able to influence thecompany's dividend policy. The dividend policy is influenced by the investment opportunity set (IOS). Size is not able to moderate the effect ofprofitability, investment opportunity set (IOS) and leverage to dividend policy.